Differential Access of Immigrant Educators to the Chilean School System: Characteristics of an Emerging Phenomenon; [el Acceso Diferencial de Los Educadores Inmigrantes Al Sistema Escolar Chileno: Características de Un Fenómeno Emergente] - Ferrada-Quezada, N (Universidad Austral de Chile, 2022)
The aim of this study was to learn how immigrant educators have been incorporated into Chilean schools, through the analysis of their participation trends, their characterization, and the exploration of group formation regarding their access to the system. Data from Directorio Oficial de Docentes (Official Directory of Teachers) were analyzed applying descriptive, inferential, and latent class analysis techniques. The participation of immigrant educators, while still low (3.200 educators, 1,3% of practicing educators in 2020), increased by 218.9% during the 2015-2020 period. They work, in a higher proportion than their Chilean peers, in urban, subsidized and private schools of high socioeconomic level. In addition, they are more likely to work as classroom teachers without positions of authority, in secondary education, teaching subjects with teacher shortage and foreign languages, and with temporary contracts, than their Chilean peers. Four groups were identified, working in different socioeconomic contexts and with markedly different roles and conditions, suggesting differential access to the system. © 2022, Estudios Pedagogicos. All Rights Reserved.